(untitled) (Fiep Bulletin - online, 2014)
In search of our professional identity, as instructors, we have been evidencing a lack of definition of the current purpose of the teachers’ work, fact that provides an absence of clarity about own formation process of professional performance and also the philosophical, epistemological and ontological basis of these processes. Professionalization is a qualification process in which an organized occupation obtains exclusivity rights to the executions of a particular type of work and professionalism is linked to quality and commitment of the professional exercise. Professionalization with professionalism implies in a complex development of the profession, while systematic, multidimensional, dynamic and continuous, individual and collective process. We consider important that teaching understood as a process of professional performance and that professionalism the situation that guarantee us the necessary quality. To achieve our Professionalization with professionalism it is necessary to guarantee quality, as much as for initial development as for the instructors continuity that already perform on scholarized education, because it is an ethical and moral commitment, will guarantee credibility, professional dignity and survival of the professional field.